The Palemonids, Gediminids, and Samogitians: Some Remarks on Lithuanistics in the Chronicle of the Grand Duchy of Lithuania and Samogitia - Saviščevas, Eugenijus (Lietuvos istorijos studijos, 2021)
The article examines the hypothesis on the possible influence of a Samogitian nobleman on the author of the chronicle of the Grand Duchy of Lithuania and Samogitia. In the chronicle Lithuania and its ruling dynasty are traced back to Samogitia. The tradition of Gediminids’ pagan names in Samogitia suggests that the author of the chronicle was looking for an informer in this region and perhaps used the local naming tradition to create the names of the legendary Palemonids. The plot of the 1440 Samogitians Uprising, which appears in the Bychowec chronicle, as well as some indirect references, suggest that Stanislovas Orvydas may have been the informer.